PENGARUH KUALITAS PELAYANAN DAN BRAND EQUITY TERHADAP LOYALITAS PELANGGAN: STUDI KASUS SIPPIN CABANG BALIGE - Genaldo Pakpahan; Avoan Nababan; Tresy Sitio; Santi Agustina Manalu (STKIP Subang, 2025)
This study aims to analyze the effect of service quality and brand equity on customer loyalty at Sippin Balige, which operates in a competitive tourism-based market environment. This study addresses the empirical gap where service quality and brand equity are rated highly by customers, but do not significantly shape loyalty. Using a quantitative approach and involving 200 respondents, data were collected through a Likert scale questionnaire and analyzed through validity and reliability tests, classical assumption tests, multiple linear regression, and bootstrapping. The results show that service quality and brand equity have a positive but insignificant effect on customer loyalty, both partially and simultaneously. Bootstrapping analysis reinforced these findings, where the coefficient estimates were stable but the confidence intervals still crossed zero. These findings indicate that customer loyalty is not only determined by service quality and brand equity, but is also influenced by other factors. This study makes a theoretical contribution by highlighting the paradox between positive customer perceptions and low loyalty in the context of the contemporary beverage industry in tourist areas such as Balige.